SYNERGY OF TECHNOLOGY, FINANCIAL LITERACY, AND PARTNERSHIP IN BOOST THE PERFORMANCE OF MSMES IN BERINGHARJO MARKET, YOGYAKARTA - Sri Lestari Yuli Prastyatini; Alfonsus Fulgentius Ama Dunga (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study aims to examine the influence of technology, financial literacy, and partnerships on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Beringharjo Market, Yogyakarta. The population in this study was Beringharjo Market. Using quantitative methods and data collection through questionnaires from MSMEs, The samples were taken using the convenience sampling method. This study shows that the three variables have a positive and significant influence on MSME performance. The results of the analysis using the SPSS version 25 program shows that the variables of technology, financial literacy, and partnerships together explain 95.5% of the variation in MSME performance, emphasizing the importance of integrating these three factors in increasing competitiveness and business sustainability in traditional markets. These findings are expected to serve as a reference for business actors, students, and young entrepreneurs in developing their businesses through improving technology, financial literacy, and strategic partnerships. This study provides a new contribution by integrating technology, financial literacy, and partnerships in the context of MSME performance in Indonesia, especially in Yogyakarta. The difference between this study and previous studies is that this study uses three different independent variables from previous studies, which consist of technology, financial literacy, and partnerships. Meanwhile, for the dependent variable, the researcher uses the performance of community MSMEs in the city of Yogyakarta. In addition, there are still differences from the results of each previous study, so the performance of community MSMEs remains an interesting topic for further research.